Polynitroethyl‐ and Fluorodinitroethyl Substituted Boron Esters. Issue 36 (26th July 2013) - Klapötke, Thomas M.; Krumm, Burkhard; Moll, Richard
Abstract The reaction of boron oxide with various nitro‐substituted ethanols (2‐nitroethanol, 2‐fluoro‐2, 2‐dinitroethanol, 2, 2, 2‐trinitroethanol) furnished the corresponding nitroethyl borates B(OCH2CH2NO2)3 (1), B(OCH2CF(NO2)2)3 (2), and B(OCH2C(NO2)3)3 (3). Fluorination of the anion [(NO2)2CCH2OH]− (4) resulted in 2‐fluoro‐2, 2‐dinitroethanol (5), a precursor for 2, and was thoroughly characterized. An interesting condensation was observed with the anion 4 to form the unusual dianion [(NO2)2CCH2C(NO2)2]2− (6). All compounds were fully characterized by multinuclear NMR spectroscopy, vibrational spectroscopy (IR, Raman), mass spectrometry and elemental analysis. The chemical, physical and energetic properties of 1–3 and 5 are reported, as well as quantum chemical calculations at the CBS‐4M level of theory to predict the enthalpies and energies of formation. X‐ray diffraction studies were performed, and the crystal structures for compounds 1–6 were determined and discussed thoroughly. The boron esters 1–3 are of interest as possible candidates for smoke‐free, green colorants in pyrotechnic applications, and in case of 2 and 3 also as promising high energy oxidizers.